A method for preparing TiB by refining matrix grains using La element 2 Method for particle reinforced aluminum matrix composite material
TiB2 particles were generated in situ in the aluminum alloy matrix by the double melt mixing method, and the grains were refined using La elements, which solved the problems of reduced tensile strength of aluminum alloys and uneven distribution of TiB2 particles at high temperatures, significantly improved the mechanical properties of the material, and was suitable for structural design under high-temperature service conditions.
Patent Information
- Application Number
- CN202411117195.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-08-15
AI Technical Summary
The tensile strength of existing aluminum alloys is greatly reduced at high temperatures, and the distribution of TiB2 particles in the aluminum alloy matrix is uneven, resulting in insufficient material performance to meet the structural design and safety requirements under high-temperature service conditions.
The double melt mixing method is used, and lanthanum hexaboride and aluminum-titanium alloy are used as the source of TiB2. The melting point of lanthanum hexaboride is reduced through ice crystals, and the reaction is controlled to generate TiB2 particles in situ in the aluminum alloy matrix to ensure their uniform distribution, and the grain size of the aluminum alloy matrix is refined using La elements.
The uniform distribution of TiB2 particles in the aluminum alloy matrix is achieved, the tensile strength and yield strength of the material are improved, the comprehensive mechanical properties of the material are enhanced, and the structural design and safety requirements under high-temperature service conditions are met.
Smart Images

Figure CN118996192B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of high-strength and high-toughness aluminum-based composite materials, and in particular to a method for preparing a TiB2 particle-reinforced aluminum-based composite material by refining matrix grains with La elements. Background Art
[0002] Lightweight and high-strength materials have always been the goal of human beings' unremitting pursuit of new materials. Aluminum and its alloys have excellent properties such as light weight, high specific strength, corrosion resistance, and easy recycling. They are widely used in aerospace, national defense, transportation, electricity and other fields, and have become one of the important pillar materials for the development of the national economy. With the development of various fields towards lightweight, modernization, and high speed, especially the development requirements of "replacing steel with aluminum", the demand for high-performance, lightweight, high-strength and tough aluminum alloys is becoming increasingly strong, and the performance of existing single aluminum alloys can no longer fully meet the application requirements. Taking 7075 aluminum alloy as an example, its high-temperature tensile strength at 300°C is only 10% of the room temperature strength, which has become a key shortcoming restricting structural design and safe service under high-power and high-temperature service conditions. High-performance aluminum alloy materials are in urgent need of development. In response to the needs of various fields, researchers have developed aluminum-based composite materials with aluminum and its alloys as the matrix and specific performance particles as the reinforcement phase. It not only retains the commonality of the aluminum matrix, but also highlights the individuality of the reinforcement phase. It has broad development space and application prospects in aerospace, national defense, civil and other fields, and has attracted widespread attention from scholars at home and abroad.
[0003] Powder metallurgy has the advantages of flexible selection of reinforcement phase, precise and controllable content, and strong designability. It is one of the main methods for preparing high-performance aluminum-based composites. Although the reinforcement phase has good wettability and interface compatibility with aluminum and its alloys, it is easy to undergo phase change or react with the aluminum matrix at high temperature, losing the inherent characteristics of the metal reinforcement particles. It has been reported in the literature that adding La elements to the aluminum alloy matrix can improve the comprehensive mechanical properties of the aluminum alloy matrix, and TiB2 powder is directly added to the aluminum alloy matrix to prepare TiB2 reinforced aluminum alloy composites. However, during the preparation process, the density of TiB2 powder is greater than that of the aluminum alloy melt. Directly adding TiB2 powder will precipitate under the block, resulting in uneven distribution of the dispersed phase.
[0004] In addition, the introduction of TiB2 particles by in-situ reaction has the advantages of good dispersibility and high interface bonding. Currently, TiB2 particles are introduced by adding KBF4 and K2TiF6 composite fluoride salts into the aluminum matrix in an in-situ reaction, but this will introduce impurities such as Al3Ti and reduce the performance of the prepared composite material. Therefore, the process of the present invention is proposed to prepare TiB2 particle dispersion reinforced aluminum alloy composite materials. Summary of the invention
[0005] In view of the above problems, the present invention proposes a method for preparing TiB2 particle-reinforced aluminum-based composite materials by refining matrix grains with La element. A dual melt mixing method is adopted, with lanthanum hexaboride and aluminum-titanium alloy as the sources of TiB2. The melting point of lanthanum hexaboride is lowered by cryolite, and the reaction between the two is controlled to generate TiB2 particles in situ in the matrix. The dispersed phase is evenly distributed inside the alloy matrix without generating impurities. In addition, the La element can refine the grain size of the aluminum alloy matrix, greatly improving the mechanical properties of the material.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a TiB2 particle-reinforced aluminum-based composite material by refining matrix grains with the La element. The method adopts a dual-melt mixing method, uses lanthanum hexaboride (LaB6) and aluminum-titanium (Al / Ti) alloy as sources of TiB2, and fine TiB2 particles generated by in-situ reaction during the smelting process are uniformly distributed in the alloy matrix, playing a role of dispersion enhancement and improving the strength and toughness of the alloy material. The mass fraction of TiB2 particles in the aluminum-based composite material is 0.5%-2.0%.
[0008] As a preferred technical solution of the present invention, the preparation method steps are as follows:
[0009] Step 1: Drying lanthanum hexaboride powder, aluminum-titanium alloy, and A356 aluminum alloy samples, wherein the weight ratio of lanthanum hexaboride, aluminum-titanium alloy, and A356 aluminum alloy is 1:2-5:20-50;
[0010] Step 2: Take two crucibles, numbered A and B, preheat the crucibles, add A356 aluminum alloy to crucible A, add aluminum-titanium alloy to crucible B, raise the temperature to 750-850°C and keep it warm for 1-3 hours to turn the alloys in the crucibles into melts;
[0011] Step 3: Mix the A356 aluminum alloy melt and the aluminum-titanium alloy melt, maintain the temperature and stir for 10-30 minutes, and then stand and keep warm for a period of time;
[0012] Step 4: Add lanthanum hexaboride and cryolite (NaAlF6) to the mixed melt obtained in step 3, wherein the amount of cryolite added is 2-5 times the weight of lanthanum hexaboride, raise the crucible temperature to 930-980°C and maintain stirring for 10-30 minutes, and then stand and keep warm for a period of time;
[0013] Step 5: Add hexachloroethane powder, degas, and skim off the residue. After the hexachloroethane reacts completely, skim off the residue.
[0014] Step 6: Add a slag remover, let it stand for a while until the slag remover reacts completely, and then remove the slag again to obtain a casting liquid;
[0015] Step 7: Pour the casting liquid into the mold for molding.
[0016] The purity of the lanthanum hexaboride powder used in the preparation method is above 99%, and the fineness is above 500 meshes; the titanium content in the aluminum-titanium alloy is 8%-12%.
[0017] Compared with the prior art, the beneficial effects of the present invention are mainly manifested in:
[0018] First, the process method proposed in the present invention innovatively introduces lanthanum hexaboride as a source of boron element, and at the same time introduces La element, which can significantly refine the grain size of the aluminum alloy matrix and significantly improve the comprehensive mechanical properties of the aluminum alloy.
[0019] Second, the innovative addition of NaAlF6 (cryolith) in the present invention can effectively lower the melting point of the reaction system, making it easier for in-situ reaction to occur to form TiB2 particles, which are more evenly dispersed in the aluminum alloy matrix, thereby improving the comprehensive mechanical properties of the aluminum alloy.
[0020] Third, compared with the process of preparing TiB2 reinforced aluminum alloy composite materials by KBF4 and K2TiF6 composite fluoride salts, in which the impurity phase Al3Ti will exist, the present invention adopts a dual melt mixing method to prepare TiB2 particle reinforced aluminum-based composite materials without introducing obvious impurity phases.
[0021] Fourth, the present invention can introduce La element while improving the mechanical properties of A356 aluminum alloy, thereby improving the mechanical properties of the material, simplifying the process flow of preparing TiB2 particle-reinforced aluminum-based composite materials, and can greatly improve production efficiency and production capacity, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a process flow chart for preparing TiB2 particle reinforced aluminum-based composite material according to Example 1 of the present invention.
[0023] Figure 2 The engineering stress-strain diagrams of aluminum-based composite materials prepared in various embodiments are shown in Figure 1. (a) is the TiB2 particle-reinforced aluminum-based composite material prepared by adding lanthanum hexaboride in Example 1, (b) is the TiB2 particle dispersion-reinforced aluminum alloy composite material prepared in Example 2, (c) is the TiB2 powder-reinforced aluminum-based composite material prepared in Example 3, and (d) is A356 aluminum alloy.
[0024] Figure 3 In the process of preparing TiB2 particle-reinforced aluminum-based composite materials in Example 1 of the present invention, TEM images of the corresponding aluminum-based composite materials before (a) and after (b) adding lanthanum hexaboride indicate the refinement effect of the La element on the grains of the aluminum alloy matrix.
[0025] Figure 4SEM image (a) and EDS analysis photo (b) of the TiB2 particle reinforced aluminum-based composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The preferred embodiments and comparative embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0027] Example 1
[0028] See also Figure 1 This embodiment proposes a method for preparing a TiB2 particle reinforced aluminum-based composite material. A vacuum melting process is used to melt and mix aluminum-titanium alloy and A356 aluminum alloy, and then lanthanum hexaboride and cryolite are added. The mixture is stirred and melted, and degassing and slag removal are performed. Finally, the mixture is molded and formed to obtain a TiB2 particle reinforced aluminum-based composite material with a mass fraction of 1.5%.
[0029] The raw materials used are: 15g NaAlF6, 5g lanthanum hexaboride ultrafine powder, 18.5g aluminum-titanium alloy (titanium content is 10%), 176.5g A356 aluminum alloy (including Si 6.5-7.5%, Mg 0.3%-0.4%, Ti 0.08%-0.2%, Sr0-0.0015%, and Al balance). Lanthanum hexaboride powder was purchased from Shanghai Aladdin Reagent Co., Ltd., A356 aluminum alloy was purchased from Hebei Xinlizhong Nonferrous Metals Group Co., Ltd., and aluminum-titanium alloy was purchased from Zhongchu (Shenyang) Northeast Nonferrous Metals Market Co., Ltd.
[0030] The preparation method steps are as follows:
[0031] Step 1: Prepare the release agent, mix the two according to the weight ratio of sodium silicate nonahydrate: zinc oxide = 1:4, and then add 2.5 times the weight of water to make it into a water emulsion, and evenly brush it on the surface of the crucible and mold.
[0032] Step 2: Dry the lanthanum hexaboride powder, aluminum titanium alloy, and A356 aluminum alloy samples at 250°C.
[0033] Step 3: Take two crucibles, numbered A and B, heat the two crucibles to 450°C and keep them warm for 2 hours, preheat the crucibles, add A356 aluminum alloy to crucible A, add Al / Ti alloy to crucible B, heat to 800°C and keep them warm for 2 hours to turn the alloys in the crucibles into melts.
[0034] Step 4: Add LaB6 and NaAlF6 (cryosite) to the mixed melt obtained in step 3, raise the crucible temperature to 950°C and stir, maintain the temperature and stir for 10-30 minutes, and then let it stand and keep warm for a while.
[0035] Step 5: Add 2g of hexachloroethane powder, degas, and remove residue. Let it stand for 15 minutes until the hexachloroethane reacts completely, and then remove the residue.
[0036] Step 6: Add 2g of slag remover, let it stand for 15 minutes until the slag remover reacts completely, then remove the slag again to obtain the casting liquid.
[0037] Step 7: placing the casting liquid into a mold for molding, and letting it stand for 5 hours to finally prepare an aluminum-based composite material, wherein the mass fraction of TiB2 particles in the aluminum-based composite material is 1.5%.
[0038] Example 2
[0039] This embodiment compares the performance of TiB2 particles prepared by using aluminum-boron alloy and aluminum-titanium alloy dual melt. The raw materials used are: 31.3g aluminum-boron alloy (boron content is 3%), 18.54g aluminum-titanium alloy (titanium content is 10%), 148g A356 aluminum alloy (including Si 6.5-7.5%, Mg 0.3%-0.4%, Ti 0.08%-0.2%, Sr 0-0.0015%, Al balance), A356 aluminum alloy was purchased from Hebei Xinlizhong Nonferrous Metals Group Co., Ltd., and aluminum-boron alloy and aluminum-titanium alloy were purchased from Zhongchu (Shenyang) Northeast Nonferrous Metals Market Co., Ltd.
[0040] The preparation method steps are as follows:
[0041] Step 1: Prepare the release agent, mix the two according to the weight ratio of sodium silicate nonahydrate: zinc oxide = 1:4, and then add 2.5 times the weight of water to make it into a water emulsion, and evenly brush it on the surface of the crucible and mold.
[0042] Step 2: Drying the aluminum-boron alloy, aluminum-titanium alloy, and A356 aluminum alloy samples at 250°C.
[0043] Step 3: Heat the three crucibles to 450°C, preheat for 1.5 hours, then raise the temperature to 750°C, and put the three alloy samples into them respectively to make them molten; the aluminum-boron alloy is wrapped with aluminum foil and then put into the crucible.
[0044] Step 4: Mix the aluminum-boron alloy melt and the aluminum-titanium alloy melt, stir at 750°C for 15 minutes, and then keep it still for 15 minutes.
[0045] Step 5: Pour the mixed melt obtained in step 4 into the A356 aluminum alloy melt, stir at 750°C for 15 minutes, and then stand and keep warm for 15 minutes.
[0046] Step 6: Add 2g of hexachloroethane powder, degas, and remove residue. Let it stand for 15 minutes until the hexachloroethane reacts completely, and then remove the residue.
[0047] Step 7: Add 2g of slag remover, let it stand for 15 minutes until the slag remover reacts completely, then remove the slag again to obtain the casting liquid.
[0048] Step 8: placing the casting liquid into a mold for molding, and letting it stand for 5 hours to finally prepare an aluminum-based composite material, wherein the mass fraction of TiB2 particles in the aluminum-based composite material is 1.5%.
[0049] Example 3
[0050] This example compares the performance of TiB2 powder reinforced aluminum-based composite materials. The preparation method steps are as follows:
[0051] Step 1: Prepare the release agent, mix the two according to the weight ratio of sodium silicate nonahydrate: zinc oxide = 1:4, and then add 2.5 times the weight of water to make it into a water emulsion, and evenly brush it on the surface of the crucible and mold.
[0052] Step 2: Drying the A356 aluminum alloy sample at 250°C.
[0053] Step 3: Heat the crucible to 450°C, preheat for 1.5 hours, then raise the temperature to 750°C, put in 200g of A356 aluminum alloy sample, and make it molten.
[0054] Step 4: Weigh 3 g of TiB2 powder (Aladdin Reagent Shanghai Co., Ltd.) and add it to the melt.
[0055] Step 5: After the TiB2 powder is mixed, stir again and skim off the residue.
[0056] Step 6: Add 2g of hexachloroethane powder, degas, and remove residue. Let it stand for 15 minutes until the hexachloroethane reacts completely, and then remove the residue.
[0057] Step 7: Add 2g of slag remover, let it stand for 15 minutes until the slag remover reacts completely, then remove the slag again to obtain the casting liquid.
[0058] Step 8: placing the casting liquid into a mold for molding, and letting it stand for 5 hours to finally prepare an aluminum-based composite material, wherein the mass fraction of TiB2 in the aluminum-based composite material is 1.5%.
[0059] Table 1 Comparison of mechanical properties of aluminum-based composite materials prepared in Example 1-3 and A356 aluminum alloy
[0060]
[0061] It can be seen from Table 1 that the mechanical properties of the TiB2 particle reinforced aluminum-based composite materials (Examples 1 and 2) prepared by the dual melt method are better than those of the A356 aluminum alloy material. Compared with the TiB2 particle dispersion strengthened aluminum alloy composite material prepared without adding lanthanum hexaboride (Example 2) and the sample with direct addition of TiB2 powder (Example 3), the aluminum alloy material prepared by the dual melt method of adding lanthanum hexaboride in Example 1 has a certain improvement in tensile strength and yield strength.
[0062] from Figure 2 It can be seen that in the engineering stress-strain diagram, the jitter frequency of the tensile curve of the TiB2 particle reinforced aluminum-based composite material prepared by the method of the present invention using lanthanum hexaboride is more obvious than that of the aluminum-based composite material prepared by other methods, indicating that the aluminum-based composite material prepared by the dual melt mixing method has more fracture particles, proving that the generated TiB2 particles play a role of dispersion enhancement and improves the mechanical properties of the aluminum-based composite material.
[0063] Figure 3 In the process of preparing TiB2 particle-reinforced aluminum-based composite materials in Example 1 of the present invention, TEM images of the corresponding aluminum-based composite materials before (a) and after (b) adding lanthanum hexaboride indicate that the La element can refine the grain size of the aluminum alloy matrix, thereby greatly improving the mechanical properties of the material.
[0064] from Figure 4 It can be seen that the distribution of B element corresponds to that of Ti element. The TiB2 particles in the aluminum-based composite material prepared by the dual melt method are distributed more evenly at the interface. The generated TiB2 particles are distributed more evenly in the aluminum matrix, which plays a role of dispersion strengthening. The La element is also fully dispersed in the aluminum matrix, which plays a role in refining the grains of the aluminum alloy matrix.
[0065] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing TiB2 particle reinforced aluminum-based composite material by using La element to refine matrix grains, which is prepared by double melt mixing, characterized in that: Lanthanum hexaboride (LaB6) and aluminum-titanium (Al / Ti) alloy are used as the source of TiB2. The fine TiB2 particles generated by in-situ reaction during the smelting process are evenly distributed in the alloy matrix, playing a role of dispersion enhancement and improving the strength and toughness of the alloy material. The mass fraction of TiB2 particles in the aluminum-based composite material is 0.5%-2.0%.
2. The method according to claim 1, characterized in that Here are the steps: Step 1: Drying lanthanum hexaboride powder, aluminum-titanium alloy, and A356 aluminum alloy samples, wherein the weight ratio of lanthanum hexaboride, aluminum-titanium alloy, and A356 aluminum alloy is 1:2-5:20-50; Step 2: Take two crucibles, numbered A and B, preheat the crucibles, add A356 aluminum alloy to crucible A, add aluminum-titanium alloy to crucible B, raise the temperature to 750-850°C and keep it warm for 1-3 hours to turn the alloys in the crucibles into melts; Step 3: Mix the A356 aluminum alloy melt and the aluminum-titanium alloy melt, maintain the temperature and stir for 10-30 minutes, and then stand and keep warm for a period of time; Step 4: Add lanthanum hexaboride and cryolite (NaAlF6) to the mixed melt obtained in step 3, wherein the amount of cryolite added is 2-5 times the weight of lanthanum hexaboride, raise the crucible temperature to 930-980°C and maintain stirring for 10-30 minutes, and then stand and keep warm for a period of time; Step 5: Add hexachloroethane powder, degas, and skim off the residue. After the hexachloroethane reacts completely, skim off the residue. Step 6: Add a slag remover, let it stand for a while until the slag remover reacts completely, and then remove the slag again to obtain a casting liquid; Step 7: Pour the casting liquid into the mold for molding.
3. The method according to claim 2, characterized in that The purity of lanthanum hexaboride powder is above 99%, and the fineness is above 500 meshes; the titanium content in the aluminum-titanium alloy is 8%-12%.
Citation Information
Patent Citations
Lanthanum-hexaboride-reinforced aluminum-silicon-base composite material and preparation method thereof
CN102534314A
Enhanced titanium-based composite material and powder metallurgy preparation method thereof
CN102747249A